Psycosmogenic Patterns: A Premise for Environmental Harmony - Jakupi, Ardita Byci (European Journal of Sustainable Development, 2018)
The interest in holism is leading to new ways for development of multi-layered skills working towards a holistic integrated approach and developing new ways of multidimensional and multi-layered conceptualization of space. When the making of the place is requested, urban designers must be able to sense and interpret the visible and invisible dimension of place, in order to come to an understanding which leads to the holistic approach. Especially knowing how to recognize the invisible dimension of the site and knowing how to visualize it is one of the main challenges. This doesn’t depend only on methods or tools, but also on creativity and imagination that has a relation with experience, culture or knowledge of the architect. The following is important in most of the cases: intuition, sensitivity for the unseen, balance between the imagination, truth and the world around us. The aim of this research is to show that architects must perceive the site as a living being, as a unity of aspect of consciousness and essence, aspect of energy and vitality and aspect of physical form. Through this approach, by understanding and using of invisible patterns, we can generate sustainable concepts that lead towards environmental harmony. Keywords: Invisible patterns, perceiving, sensing, concept, environmental harmony.